Effect of ultrasonic irradiation on landfill leachate - Chua, Sze Ye. (2010)
Land filling method for the ultimate disposal of municipal solid waste material continues to be widely accepted and used due to its economic advantages of decomposition in a landfill. Landfill leachate is a type of waste water which contains high concentration of organics which are difficult-to-treat with conventional treatment methods such as biological methods due to the presence of high fraction of molecular weight compounds and refractory organics. Ultrasonic irradiation was selected due to its several advantages which include elimination on the use of chemical oxidants for the treatment of complex organic compounds, shorter reaction time, etc. The 20 kHz ultrasonic-induced reduction of chemical oxygen demand (COD) and total suspended solids (TSS) were investigated. Several operating conditions, such as power density (24 – 188 W/L), pH (2 – 11), dilution factor (1:9, 1:1 and 9:1), addition of different types and amount of catalyst (FeSO4 and CuSO4, 1.0 - 5.0 mmol/L and H2O2, 0.1 mmol/L) and powdered activated carbon (PAC, 1 - 6 g), were tested to study their effect on COD and TSS percentage reduction. Sample mineralization in term of COD and the particle rupture assessed by TSS were investigated. The optimum conditions from the operating systems were then selected together with by adding 2 g of powdered activated carbon which includes PAC/US, H2O2/PAC/US, FeSO4/PAC/US and CuSO4/PAC/US systems. Combination of ultrasonic and other treatment methods such as ultraviolet irradiation were also tested for its effectiveness in combination with ultrasonic irradiation. The treatment methods were also added with 2 g of powdered activated carbon. Overall, the best and optimum condition for the reduction of COD and TSS was PAC/US system with the reduction of 97.26 % and 65.00 %. The percentage reductions were enhanced at increased applied power densities (188 W/L), pH 7.4 (natural pH), initial leachate concentration and 2 g of PAC. The percentage reductions of the two parameters were as high as 97.26 % (PAC/US system) for COD and 87.64 % (H2O2/PAC/US) for TSS. Ultrasonic irradiation was shown to be an effective method for the reduction of COD and TSS. The total mineralization of organic pollutants by means of ultrasound irradiation alone and addition of catalysts still remains a difficult task especially for high strength wastewater such as leachate. Ultrasonic pre-treatment followed by other techniques, such as biological treatment or sonication coupled with other oxidation techniques seems to be a promising method to treat leachate in order to develop an economically more favorable integrated technique.